Spectroscopic and in silico evaluation of interaction of DNA with six anthraquinone derivatives - Ghosh, Pritha; Gurusamy, Poornima Devi; Priya, R.; Amrita, A.; Sivaramakrishna, A.; Babu, S.; Siva, R. (Applied biochemistry and biotechnology, 2013)
Anthraquinones consist of several hundreds of derivatives that differ in the nature and positions of substituent groups which are known to have several biological activities including antitumor properties. Interaction of molecules with DNA persists to be an extremely vital parameter while endeavouring to formulate therapeutics. In this study, few anthraquinone derivatives such as 1,2-dihydroxyanthraquinone (alizarin), 1,4-dihydroxyanthraquinone (quinizarin), 1,8-dihydroxyanthraquinone (danthron), 1,2,4-trihydroxyanthraquinone (purpurin), 1,4-diaminoanthraquinone, and 1-methylaminoanthraquinone were analyzed for its possible interaction with calf-thymus DNA through spectroscopy and in silico analysis. Our UV spectroscopic results indicate that all selected anthraquinones interact with DNA probably by external binding. Molar extinction coefficient has been calculated for chosen six anthraquinones. FT-IR results suggest that significant shifts of peaks as well as disappearance of certain characteristic peaks were indicators of the plausible interaction going on due to dye-DNA adduct formation. Among the six dyes used, purpurin showed better results and indicates the relatively strong binding affinity with DNA. Our molecular modeling results also show that purpurin has comparatively higher DNA interaction with a score of −6.18 compared with the ethidium bromide of −5.02 and intercalate the DNA.
Gesehen am 05.02.2020